Correlations between ovarian follicular blood flow and superovulatory responses in ewes - Oliveira, Maria E. F. [UNESP]; Feliciano, Marcus A. R. [UNESP]; D'Amato, Carla C. [UNESP]; Oliveira, Luis G. [UNESP]; Bicudo, Sony Dimas [UNESP]; Fonseca, JeferSon R.; Vicente, Wilter R. R. [UNESP]; Visco, Elise; Bartlewski, Pawel M. (Elsevier B.V., 2014)
The primary goal of this study was to employ ultrasonography to examine the ovaries of ewes undergoing superovulatory treatment for correlations between antral follicular blood flow and ovarian responses/embryo yields. Five Santa Ines ewes were subjected to a short- (Days 0-6, Group 1) and five to a long-term progesterone-based protocol (Days 0-12, Group 2) to synchronize estrus and ovulations after the superovulatory treatment. Porcine FSH (pFSH, 200 mg) was administered in 8 decreasing doses over 4 days, starting on Days 4 and 10 in Groups 1 and 2, respectively. After CIDR removal, all ewes were bred by a ram and embryos were recovered surgically 7 days later. Transrectal ovarian ultrasonography was performed the day before and on all 4 days of the superovulatory treatment. Both an arbitrary-scale [(0) non-detectable; (1) small; (2) moderate; (3) intense blood flow] and quantitative analysis of the blood flow area were used to assess the follicular blood flow in color Doppler images. There were no significant correlations between the arbitrary blood flow scores and superovulatory responses in the ewes of the present study. However, there was a positive correlation between the quantitative estimates of follicular blood flow on the final day of the superovulatory treatment, and the number (DA: r = 0.68, P< 0.05; DA/TA x 100%: r = 0.85, P< 0.05) and percentage (DA: r = 0.65, P< 0.05; DA/TA x 100%: r = 0.91, P< 0.001) of unfertilized eggs (DA: Doppler area, TA: total area of the largest ovarian cross section). This experiment presents a commercially practical tool for predicting superovulatory outcomes in ewes and evidence for the existence of follicular blood flow threshold that may impinge negatively on oocyte quality when surpassed during hormonal ovarian superstimulation. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Ewe; Superovulation; Color Doppler sonography; Blood flow; Antral follicles